MiR-126-3p Is Dynamically Regulated in Endothelial-to-Mesenchymal Transition during Fibrosis - Jordan, Nina P.; Tingle, Samuel J.; Shuttleworth, Victoria G.; Cooke, Katie; Redgrave, Rachael E.; Singh, Esha; Glover, Emily K.; Ahmad Tajuddin, Hafiza B.; Kirby, John A.; Arthur, Helen M.; Ward, Chris; Sheerin, Neil S.; et al. (International journal of molecular sciences, 2021)
In fibrotic diseases, myofibroblasts derive from a range of cell types including endothelial-to-mesenchymal transition (EndMT). Increasing evidence suggests that miRNAs are key regulators in biological processes but their profile is relatively understudied in EndMT. In human umbilical vein endothelial cells (HUVEC), EndMT was induced by treatment with TGFβ2 and IL1β. A significant decrease in endothelial markers such as VE-cadherin, CD31 and an increase in mesenchymal markers such as fibronectin were observed. In parallel, miRNA profiling showed that miR-126-3p was down-regulated in HUVECs undergoing EndMT and over-expression of miR-126-3p prevented EndMT, maintaining CD31 and repressing fibronectin expression. EndMT was investigated using lineage tracing with transgenic Cdh5-Cre-ERT2; Rosa26R-stop-YFP mice in two established models of fibrosis: cardiac ischaemic injury and kidney ureteric occlusion. In both cardiac and kidney fibrosis, lineage tracing showed a significant subpopulation of endothelial-derived cells expressed mesenchymal markers, indicating they had undergone EndMT. In addition, miR-126-3p was restricted to endothelial cells and down-regulated in murine fibrotic kidney and heart tissue. These findings were confirmed in patient kidney biopsies. MiR-126-3p expression is restricted to endothelial cells and is down-regulated during EndMT. Over-expression of miR-126-3p reduces EndMT, therefore, it could be considered for miRNA-based therapeutics in fibrotic organs.